2021
DOI: 10.1002/aic.17211
|View full text |Cite
|
Sign up to set email alerts
|

Open source implementation of glued sphere discrete element method and nonspherical biomass fast pyrolysis simulation

Abstract: In this research, a glued-sphere discrete element method was implemented in the open-source, computational fluid dynamics software MFiX. The implementation was verified using a cylinder-wall collision and then validated by simulating the packing and fluidization of nonspherical particles. The validated code was applied to simulate fast pyrolysis of nonspherical biomass particles in a bubbling fluidized bed. The glued sphere occupancy ratio was proposed to quantify the quality of shape resolution using glued sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 52 publications
(83 reference statements)
0
14
0
Order By: Relevance
“…Gao et al applied a SuperDEM-CFD solver to study the pyrolysis process of cubic biomass particles in a packed-bed reactor. Lu et al . developed a glued-sphere DEM method to investigate the biomass pyrolysis process.…”
Section: Mathematical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gao et al applied a SuperDEM-CFD solver to study the pyrolysis process of cubic biomass particles in a packed-bed reactor. Lu et al . developed a glued-sphere DEM method to investigate the biomass pyrolysis process.…”
Section: Mathematical Modelsmentioning
confidence: 99%
“…Gao et al 31 applied a SuperDEM-CFD solver to study the pyrolysis process of cubic biomass particles in a packed-bed reactor. Lu et al 35 developed a glued-sphere DEM method to investigate the biomass pyrolysis process. Wickramaarachchi and Narayana 36 built a three-dimensional Eulerian−Eulerian model and explored the pyrolysis of a single cylindrical biomass particle.…”
Section: Mathematical Modelsmentioning
confidence: 99%
“…The biochar is considered as the sum of all solid residues, including pure carbon, metaplastic species, and ash. The mass fraction of metaplastic in the biochar depends on the biomass residence time in the pyrolyzer, as the "trapped" gases are slowly released from the metaplastics (reaction [22][23][24][25][26][27][28][29][30][31]. Both TGA data and fluidized-bed pyrolyzer data were used to develop the kinetics.…”
Section: Detailed Pyrolysis Kinetic Mechanismmentioning
confidence: 99%
“…Mettler et al [23] reported that the convection, conduction, and reaction rates are all within an order of 5 magnitude of one another for a biomass particle with a diameter in the range of 100-1000 microns in a fluidized bed, thus the biomass particles usually can not be assumed isothermal. Particleresolved simulations [24][25][26] have been used to study the effect of intraparticle transport phenomena on the biomass pyrolysis products; however, it is extremely expensive to simulate millions of resolved particles in a practical reactor. Lu et al [27] proposed an offline model to couple the particle-resolved simulations with the reactor model by adding correction factors to the gas-solid heat-transfer and chemical reaction rates.…”
Section: Introductionmentioning
confidence: 99%
“…Catalytic decomposition of solid phases is a significant fundamental process in energy and environmental technologies, such as coal pyrolysis, 1,2 plastic degradation, 3,4 biomass fermentation, 5 and ammonium perchlorate (AP) decomposition 6–8 . Among these processes, AP decomposition attracts special interest due to its wide application in composite solid propellants (CSPs) for rocket 9 .…”
Section: Introductionmentioning
confidence: 99%